Control and mitigation of current harmonics in inverter‐fed permanent magnet synchronous machines with non‐linear magnetics. Issue 10 (1st August 2016) - Richter, Jan; Doppelbauer, Martin
Abstract : Inverter non‐linearities and machine spatial harmonics yield voltage errors that make harmonic current control and mitigation a challenging task. In this study, a method is presented that allows online identification and compensation of these effects to enable precise control and mitigation of current harmonics of interior permanent magnet synchronous machines with non‐linear magnetics. The method requires no additional sensors and only fundamental machine model parameters. It can be implemented easily in the control software of existing inverter systems. Test bench measurements show excellent current harmonic mitigation capability, good dynamic performance and precise control of arbitrary current harmonics. The principle is transferable to other machine types and grid applications enabling the control and mitigation of current harmonics in a wide field of applications.